Porfirio e Giamblico critici di Plotino nei commenti alle Categorie di Dexippo e Simplicio - Chiaradonna, Riccardo (Florentia Iliberritana, 2016)
Pi erre Hadot has argued that Dexippus and Simplicius in two parallel sections of their commentaries on Plotinus' criticism of Aristotle's theory of substance (Ennead. VI, 1, 1-3) probably used as sources the lost commentaries of Porphyry and Iamblichus on Aristotle's Categories. Basing the analysis upon Hadot's hypothesis, this paper aims at developing it with reference to Porphyry's and Iamblichus' different exegetical methods.